Peranan mahasiswa dalam upaya mencegah tindak pidana korupsi - Andika Wahyudi Gani; Jamil Resa (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The unique, multi-dimensional, and corrupt characteristic of corruption is one of the crimes that is difficult todismantle, because it requires steps that are carried out in extraordinary ways through its material criminal law instruments aswell as its formal crime laws. This also results in differing opinions and interpretations, both between legal differences and legaltheorists, about the limits of corruption. Various opinions given by experts and experts on corruption resolution. When viewed interms of terms, the word